Efficacy and Safety of Anti-HER2 Agents in Combination With Chemotherapy for Metastatic HER2-Positive Breast Cancer Patient: A Network Meta-Analysis - Zhang, Xiaohui; Leng, Junsheng; Zhou, Yidong; Mao, Feng; Lin, Yan; Shen, Songjie; Sun, Qiang (Frontiers in Oncology, 2021)
Background. The presence of anti-HER2 agents, such as trastuzumab, pertuzumab and trastuzumab emtansine (T-DM1) significantly improved the prognosis of metastatic HER2-positive (HER2+) BC. However, drug resistance and disease progression are still common. In order to further improve the treatment efficacy, new clinical trials about anti-HER2 agents in combination with chemotherapy are growing rapidly. We conducted the network meta-analysis to synthesize evidences of clinical trials to identify the best therapy for metastatic HER2+ BC. Methods. A systematic search of randomized controlled trials regarding anti-HER2 agents in combination with chemotherapy for advanced or metastatic breast cancers up to May 2020 was conducted in Embase, PubMed and the Cochrane Library. The primary outcome was progression-free survival (PFS). The secondary outcomes were overall survival (OS), objective response rate (ORR) and safety. Bayesian network meta-analysis was conducted to synthesize the results and rank the therapies. Results. 26 studies, including 16 studies for first line treatments and 10 studies for second or later line treatments were included in the network meta-analysis. For first line studies, the THP (taxanes + trastuzumab + pertuzumab) regimen exhibited the highest probability to be the optimal treatment in all efficacy outcomes and moderate safety. For second or later line studies, the T-DM1 and XHTuC (capecitabine +trastuzumab + tucatinib) regimens ranked top two in all efficacy outcomes according to the surface under the cumulative ranking (SUCRA) results. T-DM1 ranked the first in PFS and OS whereas XHTuC ranked the first in ORR. The safety outcomes of T-DM1 and XHTuC were acceptable. Conclusions. THP was still the optimal first line treatment for metastatic HER2+ BC. T-DM1 and XHTuC were recommended for second line treatments.